2015
DOI: 10.1038/srep16879
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanocoils synthesized through solvothermal method

Abstract: Recently helical nanostructures such as nanosprings and nanocoils have drawn great interests in nanotechnology, due to their unique morphologies and physical properties, and they may be potential building blocks in sorts of electromechanical, magnetic, photoelectronic and plasmonic devices at micro/nanoscales. In this report, multi-turns copper nanocoils were synthesized through a modified solvothermal method, in which the mixture of water and N-methyl-2-pyrrolidone (NMP) were selected as reaction medium and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…49 Numerous studies have shown that the coil/ tori SWCNTs, are more stable under high pressure than their straight ones, showing excellent mechanical strength, electrical conductivity, and persistent current (I pc ). [50][51][52][53][54][55][56][57] However, the controlled structuring of SWCNTs that have always developed as long strings into a tori-like topology may open up new 39 Copyright John Wiley and sons, 2018. application possibilities. [58][59][60] Recently, the Pickering emulsion approach has been used to synthesize a toroidal carbon nanotube (TCN) by using the pure m-and sc-SWCNTs collected from gel chromatography.…”
Section: Preferential Synthesismentioning
confidence: 99%
“…49 Numerous studies have shown that the coil/ tori SWCNTs, are more stable under high pressure than their straight ones, showing excellent mechanical strength, electrical conductivity, and persistent current (I pc ). [50][51][52][53][54][55][56][57] However, the controlled structuring of SWCNTs that have always developed as long strings into a tori-like topology may open up new 39 Copyright John Wiley and sons, 2018. application possibilities. [58][59][60] Recently, the Pickering emulsion approach has been used to synthesize a toroidal carbon nanotube (TCN) by using the pure m-and sc-SWCNTs collected from gel chromatography.…”
Section: Preferential Synthesismentioning
confidence: 99%
“…The nanowire captured in the small-sized droplet can readily be deformed into various shapes because its length can be of longer than the droplet diameter. Thus, many researchers have carried out deformation of the nanowire into a desired structure along the droplet shape: coiling of colloidal gold nanowires, carbon nanotubes (CNTs) of 500 nm in diameter induced by the contraction of their polymer shells, and copper nanocoils of 10–35 μm in diameter synthesized using a solvothermal method . These coiled gold nanowires and CNTs would go through the uncoiling process as the polymer structure was removed, whereas the copper nanocoil process is limited to specific materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many researchers have carried out deformation of the nanowire into a desired structure along the droplet shape: coiling of colloidal gold nanowires, 12 carbon nanotubes (CNTs) of 500 nm in diameter induced by the contraction of their polymer shells, 13 and copper nanocoils of 10−35 μm in diameter synthesized using a solvothermal method. 14 These coiled gold nanowires and CNTs would go through the uncoiling process as the polymer structure was removed, whereas the copper nanocoil process is limited to specific materials. The coiled ring-shaped structures can be used in tunable plasmonic resonance because of selective penetrations of electromagnetic fields through the ring cavity.…”
Section: Introductionmentioning
confidence: 99%